Ecosystem perspectives are needed to manage zoonotic risks in a changing climate. (13th November 2020) - Gibb, Rory; Franklinos, Lydia H V; Redding, David W; Jones, Kate E
Abstract : Better understanding of how environmental changes affect pathogens, hosts, and disease vectors can help prevent and respond to zoonoses, write Rory Gibb and colleagues